Study on a footwork training and testing system - Hu, Q.; Chen, Q.; Liu, Y.; Zhen, Q. (Proceedings, 2018)
In the sport science fields, for a long time there are various attempts to explore more advanced technology in order to collect kinds of information concerned during athletes training and matches. In the paper, a footwork training and testing system has been developed by adopting the advanced technology of Wireless Sensor Network (WSN). The system is comprised of some wireless senor nodes and gateways, system control software and so on. By means of the system, the daily footwork training methods and modes will be simulated to automatically guide the training of the athletes, at the same time the training data concerned will be automatically recorded, including moving velocity, moving frequency and success average, moving exercise duration and so on, and it is facilitate to evaluate digitally the training and testing effects for coaches and athletes. The system will bring about an auxiliary means in sport science training and research, make coaches and researchers have more options for the technical and information forms, and provide the technology foundation for synchronizing and intermingling the training and testing smoothly.